Values and value orientations of a digital leader in the digital economy era - E. G. Karpova; E. S. Gurenko (Цифровая социология, 2022)
The article examines the values and value orientations of a modern leader in the digital economy, in particular, the characteristics, skills and competencies, which distinguish a “digitalˮ leader from a “traditionalˮ leader and guarantee him/her success in business. The research is based on the results of a survey in which 120 people of different age categories and different managerial ranks (in Russia and abroad) participated to identify their priority personal and professional values and assess how these values influence their managerial decisions and the actions they take to transform of their business caused by digital change and the pandemic crisis and to achieve success. The findings of the study have to help understand to current and future leaders, what they have to do, what qualities and skills they have to develop to remain successful in today’s realities.